2021
DOI: 10.36103/ijas.v52i1.1234
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides Bioaccumulation and Their Soil Pollutant Effect

Abstract: This study was aimed to investigate pesticides bioaccumulation and their soil pollutant effect. The experiment was included sixteen active greenhouses in Erbil plane, and conducted during September 2017 and March 2018. The present study revealed that the pesticides residue of pyridabine, thiamethoxam, abamectin and spirodiclofen were detected in greenhouse soil samples.   The values of soil heavy metals contaminations factor (CF) revealed, that the studied greenhouse soil samples were ranged from low to very h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The stomata are present only on the lower surface. Lower epidermis rban and industries area constantly charge the environment with toxic compounds, thousands of organic trace contaminants have been generated and partially discharged into the environment over the previous few decades (18). Numerous industrial activities damage Ⅲ various environmental components such as water, air, soil, and plant growth (5).…”
Section: Resultsmentioning
confidence: 99%
“…The stomata are present only on the lower surface. Lower epidermis rban and industries area constantly charge the environment with toxic compounds, thousands of organic trace contaminants have been generated and partially discharged into the environment over the previous few decades (18). Numerous industrial activities damage Ⅲ various environmental components such as water, air, soil, and plant growth (5).…”
Section: Resultsmentioning
confidence: 99%
“…While disagreed with Charalabopoulos et. al., who reported a non-significant change in salivary antioxidants defence mechanisms [29].…”
Section: Characteristicmentioning
confidence: 99%
“…Using ntBlast, similar sequences of other microorganisms were retrieved from GenBank and compared to the 16S rRNA sequence of the isolates. The PCR results showed that the replicated isolate had a 1500 bp band ,Figure (5). The 16S ribosomal RNA gene was sequenced using this band [24].…”
Section: Molecular Characterization Of Pesticide-degrading Bacteria No37mentioning
confidence: 99%
“…Pesticides' long-term effects on people include carcinogenicity, mutagenicity, reproductive toxicity, and other health issues [3]. Therefore, Pesticide residues are regarded as a major risk factor in society which also affects used on the farmers there that spray it in greenhouse fields [4,5]. Imidacloprid (1-[(6-chloro-3-pyridinyl)-methyl]-N-nitro-2-imidazolidinimine) is a systemic neonicotinoid insecticide with the chemical compound chloronicotinyl that's used to prevent biting and sucking insects [6].…”
Section: Introductionmentioning
confidence: 99%